The Impact of TikTok Content Exposure on the Shift in Indonesian Language Use in Adolescents’ Writing Skills through a Deep Learning Approach - Istiqomah, Nurhikmawati; Nurwahyuni, Nurwahyuni; Inayah, Az Zahra Nurul; Sarina, Sarina; Dewi, Anita Candra (The Future of Education Journal, 2026)
The development of TikTok as one of the most dominant social media platforms has transformed adolescent communication patterns, including written language practices. This study aims to analyze the influence of exposure to TikTok content on shifts in Indonesian language use in adolescent writing skills through an immersive learning perspective. The research focuses on the increasing use of slang, digital abbreviations, code-mixing, and viral terms, which have the potential to impact the quality of formal writing. This study employed a qualitative descriptive method supported by literature review and surveys. Data were obtained through observations of adolescents' digital activities, analysis of writing samples, and the distribution of questionnaires regarding the intensity of TikTok use. The results indicate that high exposure to TikTok contributes to language shift through the dominance of informal vocabulary, decreased grammatical accuracy, and increased use of digital expressions in academic and semi-formal writing. However, the application of immersive learning in language education can strengthen critical literacy, awareness of linguistic context, and reflective writing skills. This study concludes that TikTok has a dual impact: passive consumption can accelerate deviation from standard Indonesian, while critical use can make it an innovative learning medium. The novelty of this research lies in the integration of sociolinguistic perspectives and immersive learning pedagogy in addressing adolescent literacy challenges in the digital age.